A triangle inequality for angles in a hilbert space (1976)
Let  x,y,z be unit vectors in a Hilbert space, and define the angle θxy by cos θxy  = Re (x,y), 0 ≤ θxy ≤ π.  The object this note  is to give a proof of the following inequality (1)                   θxz   and lt; θxy  + θyz .